ERROR ANALYSIS ON THE USE OF CONJUNCTION IN STUDENTS’ WRITING RECOUNT TEXT AT VOCATIONAL STATE SCHOOL 41 JAKARTA - Geraldine, Vincensia (Journal of Language and Literature, 2018)
This research is conducted to find out the conjunction usage within the students’ writing assignments of vocational state school. The aims of this research are to find out the common errors on the use of conjunction in their writing, investigate types of errors that occur most frequently in students’ writing proposed by Ong in Taxonomy Cohesion, and categorizing the causes of errors using the theory proposed by Richard. The research discussed about error analysis on the use of adversative (but), additive (and), and causal (because, so) in students’ writing. This research used the qualitative method and the data source comes from the tenth-grade students’ assignments. The result of this research shows that the common errors in the use of conjunction in students’ writing were a conjunction and, followed by but, so, and because. Furthermore, frequent types of error occurred in the text error of misuse is the most types of errors occur within the students’ writing assignments and then followed by the error of redundant repetition, omission, and unnecessary addition. There are three causes of errors, which are; incomplete application of rules, ignorance of rules restriction, and over-generalization. The errors of misuse and omission found out in the data, is most likely caused by the incomplete application of rules. The error of unnecessary addition and redundant repetition were caused by the ignorance of rules restriction and over-generalization.